Analysis of the glymphatic system function in high-grade glioma patients using diffusion tensor imaging along perivascular spaces - Bin Tian; Xili Jiang; Xin Luo; Wei Zhang (BMC Neurology)
Abstract Objectives This study seeks to determine if patients with high-grade glioma (HGG) demonstrate glymphatic system (GS) impairments using Diffusion Tensor Imaging Along Perivascular Spaces (DTI-ALPS). Additionally, it aims to examine the factors affecting GS performance and their implications for HGG prognosis. Methods The study enrolled fifty HGG patients alongside fifty age- and sex-matched healthy individuals. Each participant underwent diffusion tensor imaging with a Philips 3.0T MRI scanner to assess and compute the ALPS index within perivascular spaces. Variables such as gender, grade, location, volume, peritumoral edema volume, mass-edema index (peritumoral edema volume/tumor volume) and ALPS index were recorded. The Student’s t-test and rank sum test compared the ALPS indices between HGG patients and healthy controls to evaluate hemispheric differences. Linear and multivariate Cox regression analyses were utilized to discern factors influencing the ALPS index and to establish independent prognostic markers for HGG, respectively. Results The ALPS indices in both hemispheres were significantly lower in HGG patients, with the ipsilateral hemisphere exhibiting further reduced levels than the contralateral (P < 0.001). In comparisons involving tumor and edema volumes, no significant variations were observed between the hemispheres within HGG patients harboring larger tumors (P = 0.079) or lesser edema volumes (P = 0.24). A decrease in postoperative ALPS indices compared to preoperative figures was noted (P < 0.001). Univariate linear regression indicated a negative relationship between the ipsilateral ALPS index and peritumoral edema volume (P = 0.0392). Kaplan-Meier analysis demonstrated shorter survival times in patients with lower ALPS indices. Moreover, multivariate Cox regression highlighted tumor grade (HR = 1.548, P = 0.023) and ipsilateral ALPS index (HR = 0.040, P = 0.003) as crucial prognostic indicators. Conclusion In patients with HGG, there is impaired GS function in both hemispheres of the brain. Additionally, the impaired GS function in the tumor-side hemisphere is associated with tumor-associated edema. Following surgery, further damage to GS function is observed in both hemispheres of the brain in HGG patients. Poor GS function in the tumor-side hemisphere is correlated with a worse prognosis in HGG patients.